Recovery of indium and gallium from synthetic leach solution of zinc refinery residues using synergistic solvent extraction with LIX 63 and Versatic 10 acid - Sankum Nusen (2018)
Copyright © 2016 Published by Elsevier B.V. All rights reserved. A synergistic solvent extraction (SSX) system consisting LIX 63 and Versatic 10, which are both commercially available, was selected to recover both Ga(III) and In(III) from synthetic sulfate leach solutions of zinc refinery cementation residues in one circuit. With the optimum composition of the SSX system, 86% In(III) and 92% Ga(III) were extracted in a single contact at pH 3.0. The extraction and stripping kinetics of In(III) and Ga(III) were fast at 40 °C. In(III) and Ga(III) were stripped readily using solution with low acidity of 0.05 M H2SO4. Based on the McCabe-Thiele diagrams constructed, 4 stages of extraction at an A/O ratio of 1.2 and 3 stages of stripping at an O/A ratio of 5 are required for the extraction and stripping of both In(III) and Ga(III). The synergistic effect on In(III) extraction was significant while that on Ga(III), extraction was insignificant. A conceptual flowsheet is proposed including the SSX system consisting of reagents that are all commercially available and offers the advantages of recovering both In(III) and Ga(III) in one circuit and stripping with low acidity solutions.